Transformational Leadership Style terhadap Intention To Stay pada Perusahaan X saat Pandemi Covid-19 - Abi Rafdi Furqoon (STKIP PGRI SITUBONDO, 2022)
During the Covid-19 pandemic, free market conditions experienced an increase and decline in the economic field. Free market / Free Trade Agreement (FTA) is a form of cooperation between developed and developing countries to increase trade activities . Leadership style can influence the intention to stay of employees who work in a company. This research practices a quantitative approach. Retrieval of data using a questionnaire likert scale . T eknik sampling using purposive sampling . Data analysis using path analysis results ( Path Analysis ). H acyl from the hypothesis testing conducted in this study: 1) E-Trust has no significant effect on Intention to stay 2) Employee Commitment significant effect on Intention to stay 3) E-Trust significant with respect to Transformational Leadership 4) Employee Commitment significant effect on Transformational leadership 5) Transformational Leadership significant effect on Intention to stay .